2009
DOI: 10.2193/2008-107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enhanced Nutrition on Mule Deer Population Rate of Change

Abstract: Concerns over declining mule deer (Odocoileus hemionus) populations during the 1990s prompted research efforts to identify and understand key limiting factors of deer. Similar to past deer declines, a top priority of state wildlife agencies was to evaluate the relative importance of habitat and predation. We therefore evaluated the effect of enhanced nutrition of deer during winter and spring on fecundity and survival rates using a life table response experiment involving free‐ranging mule deer on the Uncompah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
212
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(246 citation statements)
references
References 92 publications
17
212
7
Order By: Relevance
“…Adult survival was included in terms for recruitment because we assumed that births occurred after census and that the preponderance of adult mortality occurred between census and births (i.e., during late winter). Means and standard deviations for f yr , s emb , s fwn , s 0 , and s 1 were derived from data in Bishop et al (2009). Mean and standard deviation for s 2 were derived from data in Miller et al (2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult survival was included in terms for recruitment because we assumed that births occurred after census and that the preponderance of adult mortality occurred between census and births (i.e., during late winter). Means and standard deviations for f yr , s emb , s fwn , s 0 , and s 1 were derived from data in Bishop et al (2009). Mean and standard deviation for s 2 were derived from data in Miller et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty in s emb , s fwn , s 0 , and s 1 was modeled using prior information (Bishop et al, 2009) modeled as beta distributions. Thus, to estimate s 0 we used…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing this literature, Ballard et al (2001) concluded that coyotes can be a significant mortality factor for deer, and Ballard et al (1999) suggested that coyotes have replaced wolves in their role as deer predators in parts of northeastern North America, frequently taking adults during winter as well as neonatal fawns. Although in some situations coyote predation on fawns is compensatory to other mortality factors (Bartmann et al 1992, Bishop et al 2009), it also has been shown to be additive, and therefore limiting, in other situations (Messier et al 1986, Patterson et al 2002. Notably, most research related to coyote impacts on deer has been conducted either in the historic range of the coyote or in northeastern North America where winter severity contributes to susceptibility to predation (Gompper 2002).…”
mentioning
confidence: 99%
“…There is concern that traditional migration routes may be threatened by increased levels of anthropogenic disturbance. Recent declines in mule deer populations have been reported throughout much of the West (deVos et al 2003), likely a result of long-term drought and loss or fragmentation of habitat, among other factors (Bishop et al 2009, Monteith et al 2014. Concern for mule deer populations has prompted state management agencies and non-governmental organizations (NGOs) to explore new strategies and broaden conservation efforts to enhance protection of key mule deer habitats, such as migration routes.…”
Section: Introductionmentioning
confidence: 99%